(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2023)
Conducting the education and upbringing process in an organic manner is the most important aspect of improving the quality of education. In the educational process, the teacher and the teacher cooperate towards one goal. At this stage, the teacher uses various methods and methods of stimulation. Motivation is a powerful regulator of behavior, helps accelerate the learning process and increases the student’s self-confidence. In this article, we will consider a method of revitalizing the cognitive activity of high school students by stimulating them in an interactive way.